Managerial incentives, innovation and product market competition - Zhentang Zhang (Deutsches Institut für Wirtschaftsforschung (DIW), 2002)
This paper investigates the strategic value of the managerial incentive scheme in affecting firms' incentive in R&D investment and their product market activities. Firstly, we find that in Cournot-quantity competition, owners strategically assign a non-profit-maximization objective to their managers. Consequently, managers in a delegation game invest more in cost-reducing R&D, and have higher output, lower prices and lower profits, as compared to profit-maximizers in an owner-run game. Secondly, we find that R&D collusion induces owners in a delegation game to choose more aggressive managerial incentives as compared to R&D competition, which in turn leads to increased R&D investment, reduced product prices and increased profits.
Keywords: O32; L22; D20; C72; 330; Strategic Delegation; Managerial Incentives; R&D competition and R&D collusion; Industrielle Forschung; Wettbewerb; Duopol; Führungskräfte; Leistungsanreiz; Vertrag; Anreizvertrag; Spieltheorie; Forschungskooperation; Theorie